Karakteristik Keausan dan Umur Pahat HSS Hasil QuenchingMelalui Pendinginan Nitrogen pada Proses Pembubutan Al-T-6061 - Sudjatmiko . (JURNAL MECHANICAL, 2013)
Quenching results of conventional HSS tool through nitrogen (N2), an increase of value : 3.125%, the research conducted to extract material Aluminum alloy T-6061, with the aim of: (1). age and HSS tool wear, tool life values obtained exponent (n) and tool life constants (CT), (2). know the mechanisms and types of HSS tool wear characteristics. The method used to "Test Variable Speed Machining", research conducted by vary the cutting speed (Vc) with three levels and depth of cut, feed motion (f) is constant. From the findings of this research longest tool life (tc): 0.99 minutes (Vc = 34.56 m / min), depth of cut  (a) = 0.3 mm, feeding (f) : 0,1 mm/put,the shortest age (tc): 0.93 minutes (Vc = 51.84 m / min), (a) = 0.5 mm, with temperatures on average nose tool T0C: 48.100C. nmaximum obtained exponent value = 0.043 at (a) = 0.3 mm, and nmin = 0.0254 at a = 1.0 mm. Taylor is so the value equation. V.T0,,043 = 86.51 (max) for cutting speed Vc = 34.56 m/min [(VB = 0.41 mm)] and V.T0,0254 = 86.51 (min), for cutting speed Vc = 86.39 m / min. [(VB = 0.30 mm)], (2). Tool wear characteristics of the most commonly grown, which is in the process of abrasive, Abrasion, Diffusion and edge wear (VB) and crater (KT) / very small, there is also BUE (Built Edge Up).Keywords: HSS tool, tool life, tool wear. quenching